The impacts of achievement goal orientation, dark triad, person-environment misfit, and perceived psychological safety on external hires’ deviant behaviors - Yi, Cuizhi; Zhang, Haifeng (Scientific reports, 2025)
Many organizations are unable to leverage the benefits of external hires due to the latter’s deviant behaviors. Drawing on person-environment fit and trait activation theories alongside goal orientation and dark triad personality research, we hypothesized and tested a conceptual model elucidating the mechanisms underlying deviant behaviors in this unique context. Our study, based on data from 236 external hires and their supervisors, reveals that these hires exhibit deviant behaviors when they experience a misalignment between their personal traits and the organizational environment. In particular, achievement goal orientation and dark triad traits (narcissism, Machiavellianism, psychopathy), often developed in highly competitive settings, predispose external hires to perceive poor alignment (i.e., a lack of person-environment fit) between their needs and the resources or demands of their new roles. Furthermore, perceived psychological safety in the workplace buffers the negative impact of these traits on misfit perceptions, thereby reducing the likelihood of deviant behaviors. Our findings suggest that tailored onboarding programs, a psychologically safe climate, and the promotion of open communication are essential for successfully integrating external hires and minimizing their deviant behaviors.